Ways to improve the use of donor resources in the Nizhny Novgorod Region - S. V. Romanov; O. P. Abaeva; G. Yu. Smirnova (Трансплантология (Москва))
The article analyzes the system of organ transplantation in the Nizhny Novgorod Region in order to determine the ways to optimize the use of donor resource. The authors found that the most difficult are the program activities, the success of which depends on the attitude of health care employees and the population of the region. In this regard, a questionnaire survey was conducted; its results indicated a lack of awareness among doctors and the public about the transplantation role in modern medicine and the legislation in this sphere of relations. The authors come to the conclusion on the importance of the outreach and promotion of the posthumous organ donation program among health care employees and all population groups to optimize the use of donor resource of the region.